A Systematic Review of Common Drug Review Pharmacoeconomic Submissions and an Analysis of Emerging Trends - Sabarre, Kelley-Anne (Université d'Ottawa / University of Ottawa, 2014)
Given financial constraints, drug manufacturers are required to provide pharmacoeconomic evaluations to demonstrate the value for money of their drug compared to current treatment when requesting reimbursement by publicly funded health care systems. This thesis is a retrospective examination of pharmacoeconomic evaluations submitted for review to the Common Drug Review process. Its purpose was to determine the pattern of adherence to guidelines, trends in methodological quality, and transparency, changes in the adoption and practice of sensitivity analysis and probabilistic methods, use of indirect treatment comparison, and identify methodological factors−determinants of recommendations. Using an instrument that was developed and tested, information from 201 pharmacoeconomic evaluations was collected and analysed. Pharmacoeconomic evaluations may have improved over time in terms of adherence, methodological quality, transparency, use of probabilistic sensitivity analysis and indirect treatment comparison. However, such improvements have been minimal and further efforts are needed to better improve pharmacoeconomic evaluations in the future.
Keywords: pharmacoeconomic evaluation; Common Drug Review; trends